Modern biotechnology and poor farmers in developing countries - Pinstrup-Andersen, Per (2000)
This article reviews some of the factors that may affect the development of modern biotechnology and its use by poor farmers in developing countries. These include whether the private research organizations focus on the needs of such farmers, the ability of the governments in these countries to develop appropriate environmental and public health regulatory frameworks. Economic and public policy issues relating to these topics are discussed.